Peluang Revolusi Industri 4.0 Bidang Pemasaran: Pemanfaatan Aplikasi E-commerce, Sosial Media Instagram dan Digital Marketing terhadap keputusan Instant Online Buying Konsumen Generasi Millenial - Bambang Setia Wibowo; Diaz Haryokusumo (UNIVERSITAS PGRI MADIUN, 2020)
This study examined the influence of e-commerce application, social media instagram and digital marketing to online purchases of millennial generation consumers. Respondents of this study were 152 university students who have already shopped online at e-commerce applications, have ever seen e-commerce advertisements on electronic media and have used social media instagram for online shopping participated in this reseach. There are several findings in this study. First, e-commerce application has positive influence to online purchases of millennial generation consumers. Second, social media instagram has postive effect to online purchases of millennial generation consumers. Third, digital marketing has positive effect to online purchases of millennial generation consumers.Keywords : industrial revolution 4.0, e-commerce, instagram, digital marketing, instant online buying, millennial generation consumers